How much does the COVID-19 pandemic affect the clinical attitudes and anxiety levels of Turkish dentists in their dental practice? - Duygu Göller Bulut; Gülbahar Ustaoğlu; Tuğçe Paksoy (Selçuk University, 2022)
Background: To investigate whether there is a change in the attitudes and behaviors of Turkish dentists during their dental procedures against the COVID 19 pandemic. Methods: A web-based cross-sectional survey study was directed using a "Google Form" to obtain responses from dentists during February and March 2021. The survey was composed of 4 parts including: 1. demographic data (age, sex, marital status, systemic health), scope of practice (general dental practitioner versus specialist), place of practice (private versus public), and experience; 2. questions about COVID-19 management in practice and clinic biosafety routine, 3. questions about measures taken in dentistry clinics against COVID-19 and 4. questions about knowledge, attitudes and concerns of dentists towards the COVID 19 pandemic. Results: A total of 556 dentists completed questionnaire. The rate of questioning the HES code, temperature measurement and wanting each patient to rinse their mouth with anti-bacterial mouthwash before treatment were higher for specialist dentists (p